Stopped in its tracks: how λ‐cyhalothrin can break the aphid transmission of a potato potyvirus. Issue 12 (26th January 2015) - Fenton, Brian; Salter, William T; Malloch, Gaynor; Begg, Graham; Anderson, Eric
Abstract BACKGROUND Pyrethroids are one of the most widespread and commonly used classes of insecticide and are used in multiple roles, including protecting potato crops from virus vector aphids. Resistance in some genotypes of a few species is now widespread, but most species remain susceptible. The rate of virus transmission by two genotypes of the peach potato aphid, Myzus persicae, fed on potato virus Y (PVY)‐infected leaves of potato treated with the pyrethroid λ‐cyhalothrin was evaluated. RESULTS The susceptible genotype, type J, was significantly inhibited from transmitting virus to uninfected seedlings. A genotype containing the M918L super knockdown resistance mutation conferring resistance to pyrethroids, type O, showed no inhibition of transmission. However, when survival of the aphids after exposure was compared, the pyrethroid had not killed the type J aphids. CONCLUSIONS λ‐Cyhalothrin in a commercial formulation disrupts PVY transmission by disorienting aphid vectors for a sufficient time for the virus to lose its transmissibility. However, M. persicae genotypes carrying the M918L mutation are not prevented from transmitting. © 2014 Society of Chemical Industry